Improvement of Educational Technologies as a Factor in the Development of Human Capital ("Journal "U". Economy. Management. Finance.", 2023)
In modern conditions, one of the most important factors of socio-economic development is human capital, which is an integrated indicator based on the calculation and analytical interpretation of various aspects of the social life of citizens. In turn, the qualitative characteristics of education largely determine human capital, which naturally leads to the scientific search for the most effective educational technologies that can improve the skills of employees and/or form the basis for further effective training in skills and abilities that are in demand in the socio-economic life of society. The article substantiates the use of the educational technology of bibliotherapy in the context of the development of human capital, considers the predictive socio-economic effect due to the use of this technology.
Keywords: human capital; education; technologies; bibliotherapy; social and economic development; factors; effect